Blessed Thessaly - Aston, Emma (Liverpool University Press, 2024)
Thessaly was a region of great importance in the ancient Greek world, possessing both agricultural abundance and a strategic position between north and south. It presents historians with the challenge of seeing beyond traditional stereotypes (wealth and witches, horses and hospitality) that have coloured perceptions of its people from antiquity to the present day. It also presents a complex and illuminating interaction between polis and ethnos identity. In daily life, most Thessalians primarily operated within, and identified with, their specific polis; at the same time, the regional dimension – being Thessalian – was rarely out of sight for long. It manifested itself in stories told, in deities worshipped, in modes of political co-operation, in language, rituals, sites and objects.